Competitive Intelligence Practices And Performance Of Firms Listed On The Nairobi Securities Exchange, Kenya - Waithaka, Paul (European Scientific Journal, ESJ, 2016)
Performance is critical for every listed firm, as it enhances shareholder’s value and capability to generate earnings from invested capital. Some of the firms listed on the Nairobi Securities Exchange (NSE) have been performing poorly as indicated by the rising number of firms issuing profit warnings. The competitive business environment is continuously working to drive down the rate of return on invested capital. To counter these competitive forces, firms have resorted to gathering information at their disposal and converting it into competitive intelligence through analysis and human judgment. This study sought to determine the effect of competitive intelligence practices on performance of firms listed on the NSE. Firm performance was evaluated using both financial and non-financial measures. The non-financial measures used in the study were goal achievement and customer satisfaction, while Return on Assets (ROA) and Return on Equity (ROE) were the financial measures used. The target population was the sixty firms listed on the Nairobi securities exchange. Primary data was collected using a semi-structured questionnaire; while secondary data was obtained from the firm’s published annual reports available at the NSE using a document review guide. Quantitative data was analyzed using both descriptive and inferential statistics. The findings indicate that competitive intelligence practices have a positive and a statistically significant effect on the non-financial performance of firms listed on the Nairobi Securities Exchange. The intelligence practices were found to have a positive but statistically insignificant effect on the financial performance of listed firms. Managers of listed firms should raise the utilization level of competitive intelligence practices to enable the firms to make accurate predictions on changes in the business environment, compete better in the marketplace against rivals, improve on innovation and automation, track competitors’ activities and improve the competitiveness of their firms by identifying threats and opportunities before they become obvious. The study suggests that future researches should focus on extending knowledge on competitive intelligence practices to non-listed corporate sector firms to support the generalization of the findings to all sectors in the economy.